2014
DOI: 10.1089/jmf.2013.0151
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Evidence of α2-Adrenergic Receptors in the Hypotensive Effect ofPlatonia insignisMart.

Abstract: Platonia insignis Mart. (Clusiaceae) is a medicinal plant from the Brazilian Amazon region. The present study evaluated the biological potential of the ethanol extract (Pi-EtOH) and ethyl acetate fraction (Pi-EtOAc) of the P. insignis fruit shells on the cardiovascular system of rats. Pi-EtOH or Pi-EtOAc (12.5, 25, and 50 mg/kg) was administered intravenously in normotensive rats (260-300 g), and the mean arterial pressure and the heart rate were monitored. The Pi-EtOH induced hypotension ( -11.56 -0.89, -7.43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
3
Order By: Relevance
“…The potentiation of the effect by the co-administration with L-NAME was observed. Moreover, the hypotensive effect was completely abolished by the administration of yohimbine, which indicates that the primary mechanism by which the extract promotes hypotension is via the α-adrenergic receptor (Mendes et al, 2014).…”
Section: Platonia Insignis Martmentioning
confidence: 88%
See 1 more Smart Citation
“…The potentiation of the effect by the co-administration with L-NAME was observed. Moreover, the hypotensive effect was completely abolished by the administration of yohimbine, which indicates that the primary mechanism by which the extract promotes hypotension is via the α-adrenergic receptor (Mendes et al, 2014).…”
Section: Platonia Insignis Martmentioning
confidence: 88%
“…A study performed by Mendes et al (2014) evaluated the acute hypotensive effects of ethanol extract and ethyl acetate at different doses (12.5, 25 and 50 mg/kg) from Platonia insignis fruit peel in normotensive animals. The study only demonstrated a significant reduction in the mean arterial pressure at doses of 25 and 50 mg/kg in the ethyl acetate fraction.…”
Section: Platonia Insignis Martmentioning
confidence: 99%
“…We carried out this study by conducting a clinical pharmacist intervention during lumbar foraminotomy surgery in different anesthetics stages 1,2,14…”
Section: Introductionmentioning
confidence: 99%
“…Os ensaios in vitro da atividade anticolinesterásica do ODG evidenciaram uma resposta dose-dependente, com capacidade inibitória de 67%, comparável à rivastigmina (75%), podendo ser uma alternativa terapêutica para a doença de Alzheimer(CAVALCANTE et al, 2019).A atividade antioxidante pelo método de redução do reagente cloreto de azul nitrotetrazólio em formazan foi relatada no estudode Becker et al (2018), ao avaliar a polpa do bacuri e de outras frutas nativas da Amazônia. A polpa demonstrou uma capacidade antioxidante de 78,35%, que pode estar relacionada à presença de compostos fenólicos e à grande quantidade de ácido ascórbico no fruto.Enquanto a fração acetato de etila promove efeito hipotensor mais potente, relacionado a um agonismo dos receptores α2-adrenérgicos, comprovado pela perda de efeito mediante bloqueio com ioimbina (antagonista α2)(MENDES et al, 2014).Estudos também apontam para uma ação antiparasitária dos derivados de diversas partes do bacuri. A fração diclorometano do extrato etanólico das sementes de P. insignis foi eficiente em combater as formas promastigotas de Leishmania amazonensis em modelo O efeito antihelmíntico demonstrou ser dose-dependente após incubação na presença da benzofenona, requerendo-se, uma concentração de 25 µM, durante 48 horas para alcançar a total eliminação dos parasitas, bem como esse obtém-se um tempo de ação reduzido ao elevar a dose da garcinieliptona FC.…”
unclassified